The Harish-Chandra theorem for the quantum algebra u_q (sl (3)) - Guzner, B. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A basis of a quantum universal enveloping algebra U is constructed; the following theorem is proved with the help of this basis: For any nonzero element Μ ∃ U, there exists a finite-dimensional representation π such that π(u) ≠ 0.